An institutional North Star: the role of values in presidential communication and decision-making. Issue 2 (4th March 2019) - McNaughtan, Jon; Louis, Sarah; García, Hugo A.; McNaughtan, Elisabeth D.
ABSTRACT: Mission statements have been a staple of higher education institutions for decades, but little is known of how they are used as a tool for institutional decision-making. Using three distinct data sources, this study relies on framing theory to analyse the perceptions of university presidents in the United States on the role of mission statements in deciding when and how to communicate. Further, we compare the espoused values of university mission statements to the statements university presidents made following the 2016 US presidential election. Findings indicate presidents view mission statements as central to their decision to communicate and our analysis reveals some congruence between mission statements and public statements.